Production of melanin-based plumage traits in male house sparrows: no effect of dietary copper - Stewart, Ian R.K.; Westneat, David F. (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
In many bird species, males possess conspicuous patches of black feathers on their head or breast, the size of which is often positively related to their success in intra- and intersexual interactions. The production of these plumage signals is presumed to depend upon one or more limiting factors which prevent low quality males developing large signals in order to gain the associated benefits.
Keywords: Melanin; copper; diet; plumage; Passer domesticus